A Competency Management Model to Support Digital Transformation Initiatives in a Public Organization - Ximenes, André; Alves, Carina; Vilela, Jéssyka; Jatobá, Iveruska (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2022: Anais do XXI Simpósio Brasileiro de Qualidade de Software, 2022)
Context: In recent years, public organizations are adopting new technologies and innovating processes to improve the quality of services provided to society. In the context of digital transformation, in addition to the use of new technologies, organizations need to transform their culture and acquire new competencies so that teams can change their mindset and adopt innovative work practices. Problem: Digital transformation requires changes in internal processes, as well as in the technical and behavioral skills of teams, involving new ways of evaluating and directing the professional development of employees. Method: We conducted a case study at a public organization where a competency management model was developed based on the analysis of internal documentation and discussions with the organization’s stakeholders. The evaluation of the proposed model was carried out through a focus group with 11 professionals. Results: The article describes a competency management model to support digital transformation and business process improvement projects. The competency management model includes 4 roles and 37 competencies for teams. The model includes a competency matrix to map and assess the competencies needed for each role and actions to develop new competencies. Lessons Learned: Our experience suggests that developing competencies to support digital transformation initiatives requires establishing a shared alignment and a long-term vision to ensure effective organizational learning.